Nichiren's Problematic Works - Sueki, Fumihiko 1949- (1999)
It has long been acknowledged that some works in the Nichiren corpus were not written by Nichiren but attributed to him retrospectively by later disciples. Those texts widely agreed by scholars to be apocryphal are included in a separate volume of the critical edition of his writings. The problem lies with those writings where Nichiren's authorship is disputed and whose authenticity can be neither established nor disproven. This study suggests a new method for dealing with this problematic material. It focuses on the Sandai hihō shō (On the three great secret Dharmas), a writing long controversial within the Nichiren tradition for its advocacy of an imperially sponsored ordination platform, and on essays written to the monk Sairenbō, which are important in assessing Nichiren's appropriation of original enlightenment (hongaku) thought.
Keywords: Buddhism; Dharma; Enlightenment; Forgery; Monks; Nationalism; Ordination; Political attitudes; Religious Studies; Ultimate Reality